Estrategias pedagógicas en el desarrollo de nociones espaciales en niños de cuatro años - Bazantez Escobar, Rocio del Carmen (2025)
Pedagogical strategies facilitate learning and directly develop the cognitive and later academic process of students, so it is relevant that these strategies be applied from an early age, in addition to allowing teachers to develop dynamic curricula according to the needs. of the students. The main objective of this article is to analyze the pedagogical strategies that promote the development of spatial notions in favor of four-year-old children, who are at a crucial age to understand the orientation and representation between the objects and spaces that surround them. which are fundamental for cognitive development and thus facilitate learning, among the main contextualized lines that were investigated are cognitive development, childhood, spatial notions, didactic resources and the main challenges of implementing pedagogical strategies. The qualitative approach was applied in the research, and through the documentary research technique it was possible to address each of the objectives raised in the analysis carried out. The study carried out shows that pedagogical strategies have a positive impact on the development of spatial notions in favor of children who are at the age of four. In conclusion, it should be noted that spatial notions can be developed with pedagogical, practical and interactive activities that combine structured games and manipulative materials, as long as there is personalized support from teachers.